Simulating the Impact of Income Distribution on Poverty Reduction (The Pakistan Development Review, 2015)
The traditional notion that has influenced the development thinking for almost half a century is that economic growth is fundamental to the development process, and that the objective of poverty reduction can only be achieved by allowing the benefits of growth to ultimately trickle down to the poor. The „primacy of growth‟ paradigm is based on the premise that high growth, through high investment, would lead to higher employment and higher wages, and thereby reducing poverty. The „trickle-down‟ paradigm assumes that the benefits of economic growth would, in the first round, accrue to the upper income groups, and the ensuing consumption expenditures of these households would, in subsequent rounds, accrue incomes to relatively lower income households. Importance of equity consideration in poverty alleviation efforts has been brought out of the cold and now has re-entered the mainstream development policy agenda in many developing countries. This is the consequence of a deep-rooted disillusionment with the development paradigm which placed exclusive emphasis on the pursuit of growth. During 1990s, the proliferation of quality data on income distribution from a number of countries has allowed rigorous empirical testing of standing debates on the relative importance of growth and redistribution in poverty reduction. While the debate is still inconclusive, the majority of development economists emphasised, based on empirical cross-country data, that an unequal income distribution is a serious impediment to effective poverty alleviation [Ravallion (1997, 2001)]. Many researchers suggested that growth is, in practice the main tool for fighting poverty. However, they also reiterated that the imperative of growth for combating poverty should not be misinterpreted to mean that “growth is all that matters”. Growth is a necessary condition for poverty alleviation, no doubt, but inequality also matters and should also be on the development agenda